Morphological Phylogeny of New Cretaceous Fossils Elucidates the Early History of Soil Dwelling Among Bugs - Du, Sile; Gu, Lei; Engel, Michael S.; Ren, Dong; Yao, Yunzhi (Frontiers in Ecology and Evolution, 2022)
Burrowing bugs are distinctive, beetle-like insects of the pentatomoid family Cydnidae, noteworthy for their morphological specializations for digging and a hemiedaphic life history. However, little is known about their biological significance and the early origin of soil-dwelling. Direct fossil evidence illuminating the evolutionary history of soil-dwelling in cydnids is extremely rare. Herein, we report four new species of the burrowing bug subfamily Amnestinae from mid-Cretaceous Burmese amber, including two exhibiting specialized bulldozing and digging morphological traits on the anterior of the head and forelegs. Associated morphological features and phylogenetic placement indicate that Acanthamnestus represents the earliest unequivocal soil-dwelling cydnids and pushes back the geological record of hemiedaphic true bugs to 99 Ma. Environmental evidence, the distribution of host plants, and the fossils provide a new window for understanding the early origin of soil habits in Amnestinae, and may be linked to the appearance of Moraceae.